FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN NYERI PUNGGUNG BAWAH (LOW BACK PAIN) PADA NELAYAN DI DESA BATU KARAS KECAMATAN CIJULANG PANGANDARAN - Wahab, Atthariq (Biomedika, 2019)
Data from the Ministry of Health's 2006 research on diseases and accidents that occur in fishermen and traditional divers, said that a number of fishermen on Bungin Island, West Nusa Tenggara suffered from joint pain (57.5 percent) and mild to deafness hearing loss (11.3 percent ) The results of the initial research health research on fishermen in Batukaras Village showed that the 10 most diseases were dominated by diseases related to low back pain. The aim of this study is to explore causes factor asscociation with low back pain in Batu Karas Village Community Fishermen Group. This study uses a quantitative approach with a cross sectional study design. The population in this study was the Batu Karas Village Community Fishermen Group. This sampling was carried out based on the fishermen presented at the time of the study (accidental sampling) and willing to become research respondents by filling out and signing informed consent as many as 140 respondents. Data retrieval is done by structured interviews with questionnaires. Variables that have a statistically significant relationship with the incidence of complaints of lower back pain are years of work, smoking habits, with a p-value <0.005. The conclusion of this study are the work period of more than 20 years and smoking habits associated with lower back pain.Key words: Fishermen, Low Back Pain, The Work Period, Smoking Habits